Sedentarism and Metabolic Syndrome in users of a Family Health Unit in Salvador- BA (Research, Society and Development, 2021)
Introduction: The metabolic syndrome represents a set of metabolic disorders that include endocrine and biochemical abnormalities. Objective: To measure the association between physical inactivity and metabolic syndrome in users of a Family Health Unit in Salvador-BA Materials and method: Data were collected from a previous cross-sectional study with a convenience sample. Sedentary lifestyle was the main exposure variable and MS was the outcome. Simple and absolute frequencies were obtained for all selected variables, and Odds Ratio (OR) between exposures and outcome, as well as a final model adjusted by potential confounders of the association. Results: Of the 90 participants, 58 were women and 22 were men, with 36.36% of these men and 54.39% of these women being sedentary (Group A). The average age in Group A was 50 ± 11 years. Lower income and education levels were more frequent. The prevalence of MS, according to the NCEP-ATPIII criteria, was 57.14% among sedentary people. In the group with metabolic syndrome, there was a higher frequency of hypertension, diabetes and high body mass index. There was no significant difference between physical inactivity and metabolic syndrome, even after adjusting for sex, age and alcohol consumption (OR = 1.02; CI [0.42 - 2.20]. Final considerations: Despite no association between sedentary lifestyle and MS has been detected, it is understood that the risk factors for MS and its changes are quite complex and impacting on health as a whole.